Analisis Pemasaran Pada Produk Keripik Nori di UMKM NORIbet Bandung - Salmaa Ishma Hidayati; Junianto (Jurnal Serambi Engineering, 2024)
NORIbet MSMEs is a company located in Bandung and is engaged in the processing of fishery products, one of which is seaweed. Conducting marketing analysis aims to find out how management and social processes occur in NORIbet MSMEs. The research method used is the survey method. Purposive sampling. The data collected are primary data from interviews and observations and secondary data from journals, books or other libraries. The results of this study indicate that the nori chip business is a product that can be enjoyed by all groups. NORIbet's MSME competitors are Tae Kae Noi and Mama Suka. The product is priced using cost-plus pricing and promoted through internet applications and word of mouth. Product distribution is through distributors and by placing bagged products in stalls. Production is analyzed using forecasting methods.